Motyw nadziei w twórczości Igora Talkowa - Ancerowicz, Aleksandra (Studia Rossica Posnaniensia, 2023)
The aim of this paper is to present the literary theme of hope in the works of the Soviet Russian rock poet Igor Talkov (1956–1991). The poet’s poems as well as fragments of texts from the author’s prose serve as examples. In the course of analyzing the literary legacy of the composer, the author of the article distinguishes the following images of hope: the theme of hope conditioned by striving to fulfil his role in a dignified way in the arena of life; the theme of hope for the immortality of the poet’s fame and poetry; an inverted image of hope, interpreted as a loss of delusions; the theme of hope leading to victory in the unequal struggle of two ambivalent forces: Good and Evil; the theme of hope which is faith in a better life. Moreover, the conducted research shows that the poet, recalling the literary image of hope in his work, repeatedly referred to biblical texts and the works of the authors of the Golden Age, which, as works by Igor Talkov, allows to distinguish another characteristic feature of the presented speech master.